Fluctuation and vertical distribution of a population of brown root stink bug Scaptocoris castanea (Hemiptera: Cydnidae) in the soil profile in Mato Grosso do Sul State, Brazil. - Avila, Crébio José; Modenez S. Xavier, Luciane; Santos, Viviane (ENTOMOTROPICA, 2016)
Population fluctuation and vertical distribution of the brown root stink bug, Scaptocoris castanea Perty, 1833 (Hemiptera: Cydnidae) were determined. There were two peaks of brown root stink bug (in January and September). Population peaks were in December for adults; in January and February for small and middle-sized nymphs, and in September for large nymphs. There was a significant and positive correlation (r = 0.58; p < 0.05) between rainfall and the number of insects sampled, which shows that the presence of insects in soil profile (from 0 to 0.75 cm depth) is influenced by local rainfall. Population of the stink bug is restricted to the first 45 cm soil depth during the year.